Service Quality Training to Improve Company Image at Kebab Kebab Sultan West Java - Meyrana, Tiara Andrea; Tresna, Rd Dandy (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Kebab Sultan is a business entity in the fb sector that sells various types of fast food such as kebab, burger, hot dog, sausages, french fries, and many more. Image is a picture, the public's impression of a company, an impression that is deliberately created from an object, person, or organization. The purpose of this research is to determine the role of Service Quality Training in Improving the Company's Image at Kebab Sultan West Java. The method in this research is a descriptive analysis research method with a qualitative approach used in the form of data collection techniques using field observations, interviews with the owner and staff of Kebab Sultan and documentation in the form of research evidence. The results of the research found that Service Quality Training at Kebab Sultan has had a significant effect on improving the company's image, that service quality training has the function of providing solutions related to all existing problems. The training strategy involves case discussions through an intellectual development process where staff are given knowledge in the form of material regarding services, training/practice where employees carry out direct practice of the material they have learned, and providing motivation which is expected to influence changes in employee attitudes.